Microplastics in cosmetics and personal care products : impacts on aquatic life and rodents with potential alternatives - Nur Anis Sofiah M Rahim; Farida Islahudin; Nurfaizah Abu Tahrim; Malina Jasamai (Penerbit Universiti Kebangsaan Malaysia, 2022)
Microplastics are environmental contaminants of emerging concern that are used in huge quantities in cosmetics and personal care products. As a result, microplastics are continuously released to the environment with serious implications to the ecosystem and human health. A literature search was carried out on Medline, Mendeley, Science Direct and Scopus, gathering relevant articles from 2014-2021. Common types of microplastics used in these products are polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET) and poly (methyl methacrylate) (PMMA). They are usually incorporated in toothpastes, shower gels, shampoos, creams, eye shadows, deodorants, blush powders, make-up foundations and skin creams as exfoliators, emulsifiers, binding agents, opacifying agents, anti-static agents and film-forming agents. Microplastics can cause stunted growth, infertility and low survival rate in aquatic life and they also have been linked to obesity, infertility, cancer and diabetes in humans. Major companies such as Unilever and L’Oréal have removed microplastics from their products or use the alternatives such as chitin, cellulose based microbeads and bio-based plastics. Information on long term effects of microplastics on humans is still scarce. The suitability of materials replacing microplastics and the effectiveness of campaigns and the implemented regulations are not fully evaluated. These research gaps are useful for other researchers to explore more on this subject.